Vat dye dispersing agent, application thereof and preparation method of liquid pre-reduced vat dye
By using alternating copolymer dispersants without N and S elements and homemade Rainey nickel catalysts, the problems of insufficient environmental protection risks and dispersion capabilities of existing dye dispersants are solved, and the fluidity maintenance and reaction efficiency of low-concentration dyes are achieved.
Patent Information
- Application Number
- CN202411242499.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-05
AI Technical Summary
Existing reducing dye dispersants have environmental risks and insufficient dispersion capabilities, making it difficult to maintain the fluidity of dyes at low concentrations, resulting in high production costs and increased process complexity.
Use ethylene-maleic anhydride alternating copolymer or propylene-maleic anhydride alternating copolymer as reducing dye dispersants, combining sodium hydroxide and potassium hydroxide to form an aqueous dispersant without N and S elements, and use homemade Rennie Nickel catalyst and defoaming agent are subjected to hydrogenation reduction reaction through an autoclave.
It realizes the maintenance of dye fluidity at low concentrations, reduces reaction temperature and energy consumption, improves reaction safety and production efficiency, and reduces environmental pollution.
Smart Images

Figure CN119119770A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of fine chemicals, and in particular to a vat dye dispersant and application thereof, and a method for preparing a liquid pre-reduced vat dye. Background Art
[0002] Since vat dyes are insoluble in water, they are usually dyed with reduced leuco salt yarns and then oxidized to develop color. Therefore, in the printing and dyeing industry, it is always necessary to add dispersants to the dye bath to improve the uniformity of the dye. Currently, the commonly used reduction technology routes for vat dyes include: chemical reduction, catalytic hydrogenation reduction, and electrochemical reduction. Among them, catalytic hydrogenation reduction and electrochemical reduction are more environmentally friendly and have good application prospects. However, taking indigo as an example, since indigo is insoluble in water and indigo particles swell in water, they completely lose fluidity and become solid (paste) after the concentration reaches more than 25%, which greatly limits the continuation of the reduction reaction. Therefore, in practice, the fluidity of the indigo dispersion is usually maintained by adding a dispersant.
[0003] For example, in the patent: Method for preparing indigo by catalytic hydrogenation in a fluidized bed (CN 114644585 A), the concentration of the reaction solution is increased to 25% or more by adding a dispersant (the concentration is calculated as: mass of indigo / (mass of indigo + mass of water + sodium hydroxide + potassium hydroxide) the same below), and it still has good fluidity and reactivity. However, in order to further reduce storage and transportation costs, the industry hopes that the pre-reduced reduced dye solution has a higher effective concentration. Therefore, in current patents and literature, the effective concentration is often increased to more than 30% by secondary feeding or distillation, but this undoubtedly increases the complexity of the process and increases production costs.
[0004] Most of the dispersants currently on the market for use in the dye industry are sulfonates, sulfate esters, polyacrylamides, etc., such as dispersant NNO, dispersant 5027, dispersant MF, etc. On the one hand, these catalysts contain elements such as N and S, which pose certain environmental risks; on the other hand, the dispersing ability of these dispersants is slightly insufficient. Summary of the invention
[0005] In order to solve the above technical problems, the first purpose of the present invention is to provide a vat dye dispersant, the second purpose is to provide the application of the dispersant in the preparation of vat dyes, and the third purpose is to provide a method for preparing liquid pre-reduced vat dyes. The dispersant has good dispersibility, contains no N and S elements, and reduces environmental pollution. It can maintain its fluidity when the concentration of the dye is less than 40%.
[0006] To achieve the above-mentioned first purpose, the present invention provides the following technical solution: a vat dye dispersant, characterized in that it is an aqueous solution of a copolymer and an alkali, wherein the copolymer is one or more of an ethylene-maleic anhydride alternating copolymer, a propylene-maleic anhydride alternating copolymer, and an isobutylene-maleic anhydride alternating copolymer.
[0007] In the above scheme: the alkali is one or both of sodium hydroxide and potassium hydroxide.
[0008] In the above scheme: the amount of the base added is 28%-35% of the mass of the copolymer, and the amount of the water added is 0.8-1.2 times of the mass of the copolymer.
[0009] In the above scheme: the molecular weight of the copolymer is 10-40k.
[0010] Different from graft copolymers, this copolymer is an alternating copolymer, in which ethylene, propylene, isobutylene groups and maleic anhydride groups exist alternately in its structural units. Since the basic units of the olefin-maleic anhydride alternating copolymer are hydrophobic olefin units and hydrophilic maleic acid groups after alkali dissolution, the molecule has amphiphilicity. Unlike small molecule dispersants, this dispersant can form a self-assembled structure in the dye dispersion, better wrap the dye particles and thus show better dispersibility. The dispersant contains only three elements of carbon, hydrogen and oxygen, and does not contain elements such as N and S, and has high environmental protection.
[0011] The second object of the present invention is achieved by using the vat dye dispersant in a dye reduction reaction.
[0012] The dye is one of reducing dyes such as indigo or reducing pink.
[0013] The added amount of the dispersant is 1%-2.5% of the dye mass.
[0014] The dispersant can maintain its fluidity at a dye concentration of 35%. In dye hydrogenation reduction processes, the concentration of reduced dyes can be increased to 40% without secondary feeding. It can also achieve hydrogenation reaction at a lower reaction temperature and maintain good fluidity at a lower reaction temperature. It reduces the reaction temperature, improves the safety of the reaction, and reduces the energy consumption of the reaction.
[0015] The third object of the present invention is achieved by: a method for preparing a liquid pre-reduced vat dye, characterized in that the method is prepared according to the following steps:
[0016] (1) weighing dye powder, sodium hydroxide, potassium hydroxide, and a dispersant, and putting them into water to prepare a dispersion liquid, putting the dispersion liquid into an autoclave, and adding a catalyst and a defoaming agent;
[0017] (2) After the autoclave is completely sealed, the air in the autoclave is evacuated with a vacuum pump and nitrogen is introduced until the air in the autoclave is completely replaced;
[0018] (3) Introduce hydrogen into the autoclave to a pressure of 0.2-0.8 MPa, stir, and heat to 50-60° C. After the reaction is complete, separate and recover the catalyst, and press the reduced dye solution into a container for storage.
[0019] In the above scheme: the catalyst is a homemade Raney nickel catalyst, which is prepared according to the following steps:
[0020] (1) nickel powder and molybdenum powder were mixed evenly, soaked in dilute acid for 10-15 min, then washed with deionized water until neutral, and vacuum dried to constant weight;
[0021] (2) mixing aluminum powder with dried molybdenum powder and nickel powder, and milling the mixture in a planetary ball mill at a speed of 500-1000 rpm for 30-40 min;
[0022] (3) placing the ball-milled mixed powder in a muffle furnace and setting the temperature to 250-300° C. for tempering to further stabilize the crystal phase;
[0023] (4) The alloy powder after tempering treatment is refluxed with sodium hydroxide solution for activation, the upper alkali solution is removed and the powder is washed with clean water until it is neutral to obtain an activated Raney nickel catalyst.
[0024] In the above scheme: in the Raney nickel catalyst, the mass percentage of molybdenum is 3-6%, the mass percentage of nickel is 50%, and the rest is aluminum.
[0025] After ball milling, the powder particle size is 0.1-1 μm. The dilute acid is one of dilute hydrochloric acid, dilute sulfuric acid and dilute nitric acid. In step (4), the mass concentration of the sodium hydroxide solution is 20-25%, and the reflux time is 45-60 min.
[0026] When the Raney nickel catalyst prepared by the present invention is ball milled, the metal powder is severely deformed under the collision of the steel balls in the ball mill, and is cold welded to form a lamellar structure alloy. As the ball milling collision continues, the lamellar structure becomes more and more refined. Due to the presence of a large number of crystal defects introduced by deformation and a large number of interfaces introduced by cold welding, as well as the temperature rise caused by the ball milling collision, the diffusion capacity of the components is greatly enhanced. The generation of crystal defects can enhance the adsorption behavior of hydrogen, thereby enhancing the catalytic effect.
[0027] It can be seen from XRD that the catalysts prepared by the impregnation method and the method of the present invention both have obvious nickel metal peaks, but only the catalyst of the alloy method of the present invention has an obvious molybdenum metal peak, which indicates that molybdenum exists in the catalyst in the form of a solid solution; while the peak of molybdenum in the impregnation method catalyst is not obvious, indicating that only a small amount of molybdenum is attached to the catalyst surface by impregnation. The Raney nickel prepared by the present invention has a different structure from the Raney nickel prepared by the impregnation method.
[0028] The material of the present invention is separated and the catalyst is recovered by a magnetic separator, and the magnetically separated catalyst is washed with water and then with N,N-dimethylformamide, and then put into step 1 for recycling. After every two cycles, a new Raney nickel catalyst of 0.2-1% of the mass of indigo is added.
[0029] In the preparation method of liquid pre-reduced reducing dye: the amount of sodium hydroxide added is 15-28% of the dye mass; the amount of potassium hydroxide added is 3-10% of the dye mass; the amount of Raney nickel catalyst added is 3-10% of the dye mass; the defoamer is one or more of silicone, polyether, and polyether modified polysiloxane defoamers, and the amount added is 0.1-0.5% of the dye mass.
[0030] According to the preparation method of the present invention, the reaction pressure can be reduced to 0.2-0.8MPa at the lowest, and the reaction temperature can be reduced to 50-60°C. The reaction time is 2.5-5h. The requirements for equipment and production risks are greatly reduced. In the Raney nickel catalyst of the present invention, the metal molybdenum in the alloy will not be etched by sodium hydroxide like aluminum, but will enter the nickel lattice. The addition of molybdenum changes the catalytic lattice structure, increases the number of active sites of Raney nickel and the hydrogen adsorption capacity. Under the condition of pure sodium hydroxide, a large amount of foam will be generated due to vigorous stirring, affecting the contact between the catalyst and the indigo dispersion, thereby hindering the further progress of the reaction; the generation of foam in the reaction can be avoided by adding potassium hydroxide and hydroxy silicone oil defoaming agent.
[0031] By partially replacing sodium hydroxide with potassium hydroxide, the crystallization of indigo salt can be avoided at low temperatures. When the addition amount is less than 3%, the product will become solid after being placed in a 0-degree environment for 24 hours; this phenomenon will not occur when the addition amount of potassium hydroxide is higher than 3%. In addition, in order to control costs, the addition amount of potassium hydroxide should not be too high. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The XRD diagram of Raney nickel prepared by the present invention and impregnation method. DETAILED DESCRIPTION
[0033] The present invention is further described below in conjunction with the accompanying drawings and embodiments.
[0034] Example 1
[0035] Preparation of Raney nickel catalyst:
[0036] (1) Mix nickel powder and molybdenum powder evenly, soak them in dilute hydrochloric acid for 10-15 minutes, then wash them with deionized water until they are neutral, and dry them in a vacuum dryer to constant weight. The mass percentage of molybdenum is 3%, the mass percentage of nickel is 50%, and the rest is aluminum.
[0037] (2) Mix aluminum powder with dried molybdenum powder and nickel powder, and put them into a planetary ball mill for grinding at a speed of 500-1000 rpm for 30-40 minutes. After ball milling, the powder particle size is 0.1-1 μm.
[0038] (3) The ball-milled mixed powder is placed in a muffle furnace, the temperature is set to 250° C., and tempered for 20-40 min to further stabilize the crystal phase.
[0039] (4) The alloy powder after tempering treatment is activated by refluxing a sodium hydroxide solution with a mass concentration of 21% for 45-60 minutes, removing the upper alkali solution and washing with clean water until neutral, thereby obtaining an activated Raney nickel catalyst.
[0040] Example 2
[0041] Weigh 10 g of ethylene-maleic anhydride alternating copolymer (molecular weight 15k), 3 g of sodium hydroxide, and 8 g of water, and stir and mix thoroughly to dissolve.
[0042] 100 g of indigo powder and 180 g of water were weighed and mixed to obtain an indigo paste, and 1 g of the copolymer solution was added and stirred until the mixture regained fluidity.
[0043] Example 3
[0044] Weigh 10 g of ethylene-maleic anhydride alternating copolymer (molecular weight 15k), 3.5 g of sodium hydroxide, and 12 g of water, and mix and stir thoroughly to dissolve.
[0045] 250 g of indigo powder, 55 g of sodium hydroxide, 7.5 g of potassium hydroxide, and 4 g of copolymer solution were weighed, added to 400 g of water, mixed into a liquid, and then added to a 2 L high pressure reactor, and 1 g of a defoamer and 12 g of the Raney nickel catalyst prepared in Example 1 were added.
[0046] After the high-pressure reactor is completely sealed, the air in the reactor is evacuated with a vacuum pump and nitrogen is introduced. This cycle is repeated three times until the air in the reactor is completely replaced. After 0.8MPa of hydrogen is introduced, the air inlet valve is closed, the stirring speed is adjusted to 900rpm, and the temperature is raised to 55°C. The reaction is stopped when the pressure no longer decreases. The reaction time is 3h and the temperature is lowered. After the materials in the reactor are pressed into a magnetic separator, a pre-reduced liquid indigo product and a catalyst are obtained. The catalyst is washed with water and N,N-dimethylformamide and then recovered.
[0047] The pre-reduced indigo obtained by the above method is a reddish brown liquid with a concentration of 35% and a reduction rate of 98.3%.
[0048] Example 4
[0049] Weigh 10 g of propylene-maleic anhydride alternating copolymer (molecular weight 20k), 2.8 g of sodium hydroxide, and 8 g of water, and stir and mix thoroughly to dissolve.
[0050] 250 g of reduced pink powder, 45.7 g of sodium hydroxide, 12.5 g of potassium hydroxide, and 6.25 g of copolymer solution were weighed, put into 400 g of water, mixed into a liquid, and then added into a 2 L high pressure reactor, and 1.25 g of defoamer and 12 g of the Raney nickel catalyst of Example 1 were added.
[0051] After the high-pressure reactor is completely sealed, the air in the reactor is evacuated with a vacuum pump and nitrogen is introduced. This cycle is repeated three times until the air in the reactor is completely replaced. After 0.8MPa of hydrogen is introduced, the air inlet valve is closed, the stirring speed is adjusted to 900rpm, and the temperature is raised to 60°C. The reaction is stopped when the pressure no longer decreases. The reaction time is 2.5h and the temperature is lowered. After the materials in the reactor are pressed into a magnetic separator, a pre-reduced liquid pink product and a catalyst are obtained. The catalyst is washed with water and N,N dimethylformamide respectively and then recovered.
[0052] The pre-reduced pink obtained by the above method is a reddish brown liquid with a concentration of 35% and a reduction rate of 97.9%.
[0053] Example 5
[0054] Weigh 10 g of ethylene-maleic anhydride alternating copolymer (molecular weight 40k), 3 g of sodium hydroxide, and 12 g of water, and stir and mix thoroughly to dissolve.
[0055] 250 g of indigo powder, 56 g of sodium hydroxide, 7.5 g of potassium hydroxide, and 2.5 g of copolymer solution were weighed, added into 340 g of water, mixed into a liquid, and then added into a 2 L high pressure reactor, and 1 g of defoamer and 10 g of the Raney nickel catalyst of Example 1 were added.
[0056] After the high-pressure reactor is completely sealed, the air in the reactor is evacuated with a vacuum pump and nitrogen is introduced. This cycle is repeated three times until the air in the reactor is completely replaced. After 0.8MPa of hydrogen is introduced, the air inlet valve is closed, the stirring speed is adjusted to 900rpm, and the temperature is raised to 50°C for reaction. The reaction is stopped after the pressure no longer decreases. The reaction time is 3h and the temperature is lowered. The catalyst is separated. The pre-reduced indigo obtained by the above method is a reddish-brown liquid with a concentration of 38% and a reduction rate of 97.3%.
[0057] Example 6
[0058] Weigh 10 g of isobutylene-maleic anhydride alternating copolymer (molecular weight 15k), 3.5 g of sodium hydroxide, and 12 g of water, and stir and mix thoroughly to dissolve.
[0059] 250 g of indigo powder, 53 g of sodium hydroxide, 7.5 g of potassium hydroxide, and 4 g of copolymer solution were weighed, added to 400 g of water, mixed into a liquid, and then added to a 2 L high pressure reactor, and 1 g of a defoamer and 12 g of the Raney nickel catalyst prepared in Example 1 were added.
[0060] After the high-pressure reactor is completely sealed, the air in the reactor is evacuated with a vacuum pump and nitrogen is introduced. This cycle is repeated three times until the air in the reactor is completely replaced. After 0.2MPa of hydrogen is introduced, the air inlet valve is closed, the stirring speed is adjusted to 900rpm, and the temperature is raised to 60°C. When the pressure no longer drops, the reaction is stopped, the reaction time is 5h, and the temperature is lowered. After the materials in the reactor are pressed into a magnetic separator, a pre-reduced liquid indigo product and a catalyst are obtained. The catalyst is washed with water and N,N-dimethylformamide and then recovered.
[0061] The pre-reduced indigo obtained by the above method is a reddish brown liquid with a concentration of 35% and a reduction rate of 95.5%.
[0062] Example 7
[0063] The preparation of the Raney nickel catalyst is the same as that in Example 1, except that the mass percentage of molybdenum is 6%, the mass percentage of nickel is 50%, and the remainder is aluminum.
[0064] Weigh 10 g of ethylene-maleic anhydride alternating copolymer (molecular weight 40k), 3 g of sodium hydroxide, and 12 g of water, and stir and mix thoroughly to dissolve.
[0065] 250 g of indigo powder, 56 g of sodium hydroxide, 7.5 g of potassium hydroxide, and 2.5 g of copolymer solution were weighed, added to 340 g of water, mixed into a liquid, and then added to a 2 L high pressure reactor, and 1 g of a defoamer and 10 g of the Raney nickel catalyst prepared in this example were added.
[0066] After the high-pressure reactor is completely sealed, the air in the reactor is evacuated with a vacuum pump and nitrogen is introduced. This cycle is repeated three times until the air in the reactor is completely replaced. After 0.8MPa of hydrogen is introduced, the air inlet valve is closed, the stirring speed is adjusted to 900rpm, and the temperature is raised to 60°C for reaction. The reaction is stopped after the pressure no longer decreases. The reaction time is 2.5h and the temperature is lowered. The catalyst is separated. The pre-reduced indigo obtained by the above method is a reddish-brown liquid with a concentration of 38% and a reduction rate of 98.2%.
[0067] After the products of Examples 3-7 of the present invention were placed in a refrigerator at -10°C for 24 hours, the products still remained in a liquid state and had good fluidity.
[0068] Comparative Example 1
[0069] Weigh 200 g of indigo powder, 56 g of sodium hydroxide, and 6.4 g of potassium hydroxide, add them into 400 g of water, and after mixing, the mixture loses fluidity and cannot undergo hydrogenation reaction.
[0070] Comparative Example 2
[0071] Weigh 250g indigo powder, 55g sodium hydroxide, 7.5g potassium hydroxide, 4g dispersant NNO, put into 400g water and mix as liquid and add 2L autoclave, add 1g defoamer, and add 12g Raney nickel catalyst of embodiment 1. After the autoclave is completely sealed, the air in the kettle is extracted with a vacuum pump, and nitrogen is passed through, and the cycle is repeated 3 times until the air in the kettle is completely replaced. After 0.8MPa hydrogen is passed through, the air inlet valve is closed, and the temperature is raised to 85 degrees Celsius after the stirring speed is adjusted to 900rpm. Stop the reaction after the pressure no longer decreases and cool down.
[0072] The pre-reduced indigo obtained by the above method is a viscous asphaltene semi-fluid with a concentration of 35% and a reduction rate of 2.3%, and is basically unable to undergo hydrogenation reaction.
[0073] Comparative Example 3
[0074] Weigh 190g indigo powder, 56g sodium hydroxide, 6.4g potassium hydroxide, 4g dispersant NNO, put into 400g water and mix as liquid, then add 2L autoclave, add 1g defoamer, 9g Raney nickel catalyst of embodiment 1. After the autoclave is completely sealed, the air in the kettle is extracted with a vacuum pump, and nitrogen is passed through, and the cycle is repeated 3 times until the air in the kettle is completely replaced. After 0.8MPa hydrogen is passed through, the air inlet valve is closed, and the temperature is raised to 85 degrees Celsius after the stirring speed is adjusted to 900rpm. Stop the reaction after the pressure no longer decreases and cool down.
[0075] The pre-reduced pink obtained by the above method is a reddish brown liquid with a concentration of 28.9% and a reduction rate of 96.9%.
[0076] Comparative Example 4
[0077] 200 g of indigo powder, 30 g of sodium hydroxide, 20 g of potassium hydroxide, and 2 g of dispersant NNO were weighed, put into 400 g of water, mixed into a liquid, and then added into a 2L high-pressure reactor, and 1 g of defoamer and 6 g of the Raney nickel catalyst of Example 1 were added.
[0078] After the autoclave is completely sealed, the air in the autoclave is evacuated with a vacuum pump and nitrogen is introduced. This cycle is repeated three times until the air in the autoclave is completely replaced. After introducing 0.2MPa hydrogen, close the air inlet valve, adjust the stirring speed to 500rpm, and then raise the temperature to 85°C. When the temperature in the autoclave reaches 85°C, add the hydrogen pressure to 0.3MPa and keep the valve open for continuous ventilation. Record the reaction time, speed, temperature and changes. After 3-4 hours of reaction, stop the reaction.
[0079] After the materials in the kettle are pressed into a magnetic separator, a pre-reduced liquid indigo product and a catalyst are obtained. The catalyst is washed with water and N,N-dimethylformamide respectively and then recovered.
[0080] The obtained pre-reduced indigo was a clear reddish brown liquid with a concentration of 29.4% and a reduction rate of 97.3%.
[0081] Comparative Example 5
[0082] 200 g of indigo powder, 62 g of sodium hydroxide, and 4 g of dispersant NNO were weighed, added to 400 g of water, mixed into a liquid, added to a 2 L high pressure reactor, and 9 g of the Raney nickel catalyst of Example 1 was added.
[0083] After the autoclave is completely sealed, the air in the autoclave is evacuated with a vacuum pump and nitrogen is introduced. This cycle is repeated three times until the air in the autoclave is completely replaced. After introducing 0.8 MPa hydrogen, the air inlet valve is closed, the stirring speed is adjusted to 900 rpm, and the temperature is raised to 85°C. When the temperature in the autoclave reaches 85°C, the reaction time, rotation speed, temperature and pressure changes are recorded. When the pressure no longer changes, the reaction is stopped. The recorded reaction time is 7 hours.
[0084] After the materials in the kettle are pressed into a magnetic separator, a pre-reduced liquid indigo sodium salt product is obtained.
[0085] In the experiment of Comparative Example 5, after the reaction was completed, a large amount of foam was observed when the autoclave was opened, and the product was a slightly viscous liquid with a reduction rate of 90.2%. Furthermore, after the product of Comparative Example 5 was placed in a refrigerator at -10°C for 24 hours, the product of Comparative Example 5 became solid and lost fluidity.
[0086] Comparative Example 6
[0087] Weigh 10 g of propylene-maleic anhydride alternating copolymer (molecular weight 20k), 2.8 g of sodium hydroxide, and 8 g of water, and stir and mix thoroughly to dissolve.
[0088] 250 g of reduced pink powder, 45.7 g of sodium hydroxide, 12.5 g of potassium hydroxide, and 6.25 g of copolymer solution were weighed, added into 400 g of water, mixed into a liquid, and then added into a 2 L high pressure reactor, and 12 g of the Raney nickel catalyst of Example 1 was added.
[0089] After the autoclave is completely sealed, the air in the autoclave is evacuated with a vacuum pump and nitrogen is introduced. This cycle is repeated three times until the air in the autoclave is completely replaced. After introducing 0.8MPa hydrogen, the air inlet valve is closed, the stirring speed is adjusted to 900rpm, and the temperature is raised to 60°C. Stop the reaction after the pressure no longer drops, the reaction time is 4h, and the temperature is lowered. When the autoclave is opened, a small amount of foam can be observed floating on the surface of the product and adhering to the stirring rod. After the material in the autoclave is pressed into a magnetic separator, a pre-reduced liquid pink product and a catalyst are obtained. The catalyst is washed with water and N,N dimethylformamide respectively and then recovered.
[0090] The pre-reduced pink obtained by the above method is a reddish brown liquid with a concentration of 35% and a reduction rate of 96.5%. After being placed in a refrigerator at -10°C for 24 hours, the product still maintains a liquid state and has good fluidity.
[0091] Comparative Example 7
[0092] Weigh 10 g of propylene-maleic anhydride alternating copolymer (molecular weight 20k), 2.8 g of sodium hydroxide, and 8 g of water, and stir and mix thoroughly to dissolve.
[0093] 250 g of reduced pink powder, 58.2 g of sodium hydroxide, and 6.25 g of copolymer solution were weighed, added into 400 g of water, mixed into a liquid, and then added into a 2 L high pressure reactor, and 1 g of a defoamer and 12 g of the Raney nickel catalyst of Example 1 were added.
[0094] After the autoclave is completely sealed, the air in the autoclave is evacuated with a vacuum pump and nitrogen is introduced. This cycle is repeated three times until the air in the autoclave is completely replaced. After introducing 0.8MPa hydrogen, the air inlet valve is closed, the stirring speed is adjusted to 900rpm, and the temperature is raised to 60°C. Stop the reaction after the pressure no longer drops, the reaction time is 7h, and the temperature is lowered. When the autoclave is opened, a small amount of foam can be observed floating on the surface of the product and adhering to the stirring rod. After the materials in the autoclave are pressed into a magnetic separator, a pre-reduced liquid pink product and a catalyst are obtained. The catalyst is washed with water and N,N dimethylformamide respectively and then recovered.
[0095] The pre-reduced pink obtained by the above method is a reddish brown liquid with a concentration of 35% and a reduction rate of 96.3%. After being placed in a refrigerator at -10°C for 24 hours, the product becomes solid and loses fluidity.
[0096] When the amount of potassium hydroxide added is less than 3% of the dye, the product will become solid and lose fluidity at low temperatures.
[0097] Comparative Example 8
[0098] Weigh 10 g of ethylene-maleic anhydride alternating copolymer (molecular weight 15k), 3.5 g of sodium hydroxide, and 12 g of water, and mix and stir thoroughly to dissolve.
[0099] 250 g of indigo powder, 55 g of sodium hydroxide, 7.5 g of potassium hydroxide, and 4 g of copolymer solution were weighed, added into 400 g of water, mixed into a liquid, and then added into a 2 L high pressure reactor, 1 g of defoamer and 12 g of Raney nickel catalyst prepared by the impregnation method disclosed in CN 103480394A were added.
[0100] After the high-pressure reactor is completely sealed, the air in the reactor is evacuated with a vacuum pump and nitrogen is introduced. This cycle is repeated three times until the air in the reactor is completely replaced. After 0.8MPa of hydrogen is introduced, the air inlet valve is closed, the stirring speed is adjusted to 900rpm, and the temperature is raised to 55°C. Stop the reaction after the pressure no longer drops, the reaction time is 6h, and the temperature is lowered. After the materials in the reactor are pressed into a magnetic separator, a pre-reduced liquid indigo product and a catalyst are obtained. The catalyst is washed with water and N,N dimethylformamide and then recovered. The reduction rate is tested to be 64.8%.
[0101] Comparative Example 9
[0102] The rest is the same as Comparative Example 8, except that 12 g of the Raney nickel catalyst prepared in Example 1 of CN 104056641 B is added. The reduction rate is tested to be 83.3%.
[0103] Comparative Example 10
[0104] Weigh 10 g of styrene-maleic anhydride alternating copolymer (molecular weight 15k), 3.5 g of sodium hydroxide, and 12 g of water, and stir and mix thoroughly to dissolve.
[0105] 250 g of indigo powder, 55 g of sodium hydroxide, 7.5 g of potassium hydroxide, and 4 g of copolymer solution were weighed, added to 400 g of water, mixed into a liquid, and then added to a 2 L high pressure reactor, and 1 g of a defoamer and 12 g of the Raney nickel catalyst prepared in Example 1 were added.
[0106] After the autoclave is completely sealed, the air in the autoclave is evacuated with a vacuum pump and nitrogen is introduced. This cycle is repeated three times until the air in the autoclave is completely replaced. After introducing 0.8 MPa hydrogen, the air inlet valve is closed, the stirring speed is adjusted to 900 rpm, and the temperature is raised to 55°C. The reaction is stopped when the pressure no longer decreases. The reaction time is 3 hours, and the temperature is lowered.
[0107] The pre-reduced indigo obtained by the above method is a pitch-like fluid with a concentration of 35% and a reduction rate of 8.3%.
[0108] The present invention is not limited to the embodiments. In the method for preparing vat dyes, the amount of sodium hydroxide added is 15-28% of the mass of the dye; the amount of potassium hydroxide added is 3-10% of the mass of the dye; the amount of Raney nickel catalyst added is 3-10% of the mass of the dye; the defoamer is one or more of silicone, polyether, and polyether-modified polysiloxane defoamers, and the amount added is 0.1-0.5% of the mass of the dye.
Claims
1. A vat dye dispersant, characterized in that: It is an aqueous solution of a copolymer and an alkali, wherein the copolymer is one or more of ethylene-maleic anhydride alternating copolymer, propylene-maleic anhydride alternating copolymer, and isobutylene-maleic anhydride alternating copolymer.
2. The vat dye dispersant according to claim 1, characterized in that: The alkali is one or both of sodium hydroxide and potassium hydroxide.
3. The vat dye dispersant according to claim 1 or 2, characterized in that: The added amount of the alkali is 28%-35% of the mass of the copolymer, and the added amount of the water is 0.8-1.2 times of the mass of the copolymer.
4. The vat dye dispersant according to claim 3, characterized in that: The molecular weight of the copolymer is 10-40k.
5. Use of the vat dye dispersant according to any one of claims 1 to 4 in a dye reduction reaction.
6. The use of the vat dye dispersant in dye reduction reaction according to claim 5, characterized in that: The dye is one of indigo or vat pink.
7. The use of the vat dye dispersant according to claim 6 in the reduction reaction of vat dyes, characterized in that: The added amount of the dispersant is 1%-2.5% of the dye mass.
8. A method for preparing a liquid pre-reduced vat dye, characterized in that: Prepare according to the following steps: (1) weighing dye powder, sodium hydroxide, potassium hydroxide, and a dispersant, and putting them into water to prepare a dispersion liquid, putting the dispersion liquid into an autoclave, and adding a catalyst and a defoaming agent; (2) After the autoclave is completely sealed, the air in the autoclave is evacuated with a vacuum pump and nitrogen is introduced until the air in the autoclave is completely replaced; (3) hydrogen is introduced into the autoclave to a pressure of 0.2-0.8 MPa, stirred, and heated to 50-60°C. After the reaction is complete, the catalyst is separated and recovered, and the pre-reduced dye solution is pressed into a container for storage.
9. The method for preparing a liquid pre-reduced vat dye according to claim 8, characterized in that: The catalyst is a homemade Raney nickel catalyst, which is prepared according to the following steps: (1) nickel powder and molybdenum powder were mixed evenly, soaked in dilute acid for 10-15 min, then washed with deionized water until neutral, and vacuum dried to constant weight; (2) mixing aluminum powder with dried molybdenum powder and nickel powder, and milling the mixture in a planetary ball mill at a speed of 500-1000 rpm for 30-40 min; (3) placing the ball-milled mixed powder in a muffle furnace and setting the temperature to 250-300° C. for tempering to further stabilize the crystal phase; (4) The alloy powder after tempering treatment is refluxed with sodium hydroxide solution for activation, the upper alkali solution is removed and the powder is washed with clean water until it is neutral to obtain an activated Raney nickel catalyst.
10. The method for preparing a liquid pre-reduced vat dye according to claim 9, characterized in that: In the Raney nickel catalyst, the mass percentage of molybdenum is 3-6%, the mass percentage of nickel is 50%, and the rest is aluminum.
Citation Information
Patent Citations
Preparation method of superfine indigotin dye suspension
CN102093755A
Method for preparing indigo white solution
CN102516817A
Preparation method and activation method of Raney nickel-aluminum-X catalyst specially for hydrogenation preparation of 1,4-butanediol from 1,4-butynediol
CN102744083A
Dispersant for fine ceramics
JP1988264129A
Water-based ink for stencil printing and stencil printing method
US20060074145A1
